Characterisation of alternative splice variants of PIP5K1A in the human metastatic prostate cancer cell line, LNCaP C4-2 - Roberts, Christopher / C.J. (2022)
PIP5KIα is lipid kinase of the type I phosphatidylinositol 4-phosphate 5-kinase subfamily, responsible for the generation of the majority of cellular phosphatidylinositol (4,5) bisphosphate, an important signalling molecule required for cellular membrane dynamics, vesicular transport, actin remodelling and motility. PIP5KIα functions in the growth and metastasis of prostate, breast and other tumours, and pharmacological targeting of PIP5KIα curtails these processes in mouse models. In prostate tumours there appears to be crosstalk between the PIP5KIα and androgen receptor (AR; a key driver of prostate cancer), although the molecular mechanisms and functions in disease are unclear.